The jewel in the crown [videorecording (DVD)] - Morahan, Christopher; O'Brien, Jim, 1947-2012; Pigott-Smith, Tim; Wooldridge, Susan; Malik, Art; Ashcroft, Peggy, 1907-1991; Dance, Charles; James, Geraldine, 1950-; Scott, Paul, 1920-1978 (A & E Television Networks : Distributed by New Video, 2008)
Beset by the political tension of an unsettled year, Gandhi calls for British removal from India. Police Superintendent Ronald Merrick arrests an Indian news reporter. Daphne Manner arrives from London. Merrick vents his frustrations on Kumar in a vicious jailhouse beating. Daphne gives birth. Mildred Layton prepares for her daughter's wedding. The Governor finds out about Merrick's abuse. Sarah is seduced by an officer. Susan delivers a baby boy. Tension mounts over home rule. Merrick is reassigned to Delhi. On the eve of Indian independence, Perron learns of Merrick's death. Before the independence, the Laytons and Perron prepare to return to England, leaving India to it's uncertain future.